‘Wat sal hierdie kindjie eendag word?’ Kindwees in die wêreld van Jesus (Deel 2) - Botha, P. J. J. (Verbum et ecclesia, 2000)
"What will this child become?" Childhood in the world of Jesus (Part 2) This is the second part of an historical investigation into the conditions and experiences of childhood in first century Palestine. Aspects of early childhood, socialisation and education are discussed. The issue, "Jesus and the children" is explored briefly.